Effect of Bauhinia forficata aqueous extract on the maternal-fetal outcome and oxidative stress biomarkers of streptozotocin-induced diabetic rats - Volpato, Gustavo Tadeu [UNESP]; Damasceno, Débora Cristina [UNESP]; Rudge, Marilza Vieira Cunha [UNESP]; Padovani, Carlos Roberto [UNESP]; Calderon, Iracema de Mattos Paranhos [UNESP] (Elsevier B.V., 2008)
Ethnopharmacological relevance: Bauhinia forficata Link, commonly known as paw-of-cow, is widely used in Brazilian folk medicine for the treatment of diabetes.Aim of this study: To evaluate the effect of Bauhinia forficata treatment on maternal-fetal outcome and antioxidant systems of streptozotocin-induced diabetic rats.Materials and methods: Virgin female Wistar rats were injected with 40 mg/kg streptozotocin before mating. Oral administration of an aqueous extract of Bauhinia forficata leaves was given to non-diabetic and diabetic pregnant rats at increasing doses: 500 mg/kg from 0 to 4th day of pregnancy, 600 mg/kg from 5th to 14th day and 1000 mg/kg from 15th to 20th day. At day 21 of pregnancy the rats were anaesthetized with ether and a maternal blood sample was collected for the determination superoxide dismutase (SOD) and reduced glutathione (GSH). The gravid uterus was weighed with its contents and fetuses were analyzed.Results and conclusion: The data showed that the diabetic dams presented an increased glycemic level, resorption, placental weight, placental index, and fetal anomalies, and reduced GSH and SOD determinations, live fetuses, maternal weight gain, gravid uterine weight, and fetal weight. It was also verified that Bauhinia forficata treatment had no hypoglycemic effect, did not improve maternal outcomes in diabetic rats, but it contributed to maintain GSH concentration similarly to non-diabetic groups, suggesting relation with the decreased incidence of visceral anomalies. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Bauhinia forficata; diabetes; pregnancy; reproductive outcome; anomaly; leguminosae